Kinerja Penyuluh Pertanian Lapangan Dalam Pengembangan Agribisnis Jagung Spesifik Lokasi Di Kabupaten Kubu Raya - Komariyati, Heru Chandra, Ani Muani, (Jurnal Social Economic of Agriculture, 2018)
Agricultural extension workers have an important role in the development of agribusiness corn. This study aims to determine the performance of agricultural extension, the level of conformity of maize cultivation technology, analyze the relationship between the performance of the agricultural extension with maize cultivation technology specific location in Kubu Raya. The study population was a corn farmer in Sungai Raya and Rasau Jaya subdistrict, further sampling in this study is determined in proportion to the significance level of 10 percent of the population studied corn growers. The sampling method using the formula slovin. Analyzer used to measure the performance of agricultural extension field and the level of suitability of maize cultivation technology specific location using scoring techniques while to measure the relationship of closeness between them using the Spearman rank correlation analysis. The results showed that the performance of good agricultural extension category field, specifically maize cultivation technology locations lacking categorized in accordance with the advice and performance of agricultural extension field very real touch with the low category in maize cultivation technology specific.Keywords :      Performance, agricultural extension, adoption of technology, cultivation of corn, Specific locations